2021
DOI: 10.1038/s41598-021-81944-8
|View full text |Cite
|
Sign up to set email alerts
|

Modified conditioning regimen with idarubicin followed by autologous hematopoietic stem cell transplantation for invasive B-cell non-Hodgkin’s lymphoma patients

Abstract: High-dose chemotherapy followed by autologous hematopoietic stem cell transplantation (ASCT) is still a consolidation treatment choice for relapsed/refractory B-cell non-Hodgkin’s lymphoma (NHL) patients and some aggressive B-cell NHL as frontline therapy. Due to the shortage of carmustine, we switched to idarubicin-substituted BEAC (IEAC) conditioning regimen. We retrospectively compared the outcomes of 72 aggressive B-cell NHL patients treated with IEAC or BEAC regimens followed by ASCT as upfront consolidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Although idarubicin is a new anthracycline with high efficacy and low cardiotoxicity compared to daunorubicin, cardiotoxicity remains a significant concern in patients treated with CEAC and IEAC regimens. In this study, grade 3–4 TRAEs were similar to those reported in the published literature 29 , and the TRM rate was only 3.8%. Although 2 patients who received CEAC regimen died of cardiotoxicity, the incidence of cardiotoxicity and TRM rate were not significantly different among the three groups ( P > 0.05).…”
Section: Discussionsupporting
confidence: 90%
“…Although idarubicin is a new anthracycline with high efficacy and low cardiotoxicity compared to daunorubicin, cardiotoxicity remains a significant concern in patients treated with CEAC and IEAC regimens. In this study, grade 3–4 TRAEs were similar to those reported in the published literature 29 , and the TRM rate was only 3.8%. Although 2 patients who received CEAC regimen died of cardiotoxicity, the incidence of cardiotoxicity and TRM rate were not significantly different among the three groups ( P > 0.05).…”
Section: Discussionsupporting
confidence: 90%
“…BEAM (carmustine, etoposide, cytarabine, and melphalan), CBV (carmustine, cyclophosphamide, and etoposide), and BEAC (carmustine, etoposide, cytarabine, and cyclophosphamide) are commonly used conditioning regimens. Our previous study showed that idarubicin-substituted BEAC (IEAC)-conditioning regimens were well tolerated in patients and had similar OS and PFS as BEAC regimen [28]. However, owing to the limited data provided by the original study, this meta-analysis failed to analyze the heterogeneity caused by the condition regimens.…”
Section: Discussionmentioning
confidence: 99%